1991
DOI: 10.1016/s0022-5347(17)38246-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracavernous Injection of Prostagland in E1 in combination With Papaverine: Enhanced Effectiveness in Comparison With Papaverine Plus Phentolamine and Prostaglandin E1 Alone

Abstract: We compared the erectile response to intracavernous injection of a combination of papaverine and prostaglandin E1 with that of a combination of papaverine and phentolamine (49 patients), and prostaglandin E1 alone (38). The degree of erection achieved was significantly better with papaverine plus prostaglandin E1 than with papaverine plus phentolamine and the duration of erection was less, although the incidence of prolonged erections (greater than 5 hours) was similar with both combinations. Papaverine with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Therefore a better response may be achieved with a combination of intracavernous alprostadil and other intracavernous agents than with intracavernous alprostadil alone because of additive or synergistic effects. [69] One study with 20 patients with ED has compared the efficacy of the combination of papaverine 9mg and phentolamine 0.5mg with that of the combination of alprostadil 51lg, papaverine 4.5mg and phentolamine 0.25mg after intracavernous administration. [67,68] Results of a nonblind, randomised, crossover study in 38 patients with ED of mainly vascular Abbreviations and symbols: ED = erectile dysfunction; NR = not reported; " indicates no significant difference in efficacy; > indicates significantly greater efficacy (p < 0.01 or p < 0.05); < and> indicate a trend towards lower and greater efficacy, respectively.…”
Section: Combination With Other Erectogenic Agentsmentioning
confidence: 99%
“…Therefore a better response may be achieved with a combination of intracavernous alprostadil and other intracavernous agents than with intracavernous alprostadil alone because of additive or synergistic effects. [69] One study with 20 patients with ED has compared the efficacy of the combination of papaverine 9mg and phentolamine 0.5mg with that of the combination of alprostadil 51lg, papaverine 4.5mg and phentolamine 0.25mg after intracavernous administration. [67,68] Results of a nonblind, randomised, crossover study in 38 patients with ED of mainly vascular Abbreviations and symbols: ED = erectile dysfunction; NR = not reported; " indicates no significant difference in efficacy; > indicates significantly greater efficacy (p < 0.01 or p < 0.05); < and> indicate a trend towards lower and greater efficacy, respectively.…”
Section: Combination With Other Erectogenic Agentsmentioning
confidence: 99%
“…Based on information from the 16 studies that provide information [9,19,26,27,36,37,41,44,56,58,61,65,[71][72][73]97], the frequency of hematoma/ecchymosis after intracavernosal PGEi is calculated to be 1.5% (Table 5). Based on information from the 16 studies that provide information [9,19,26,27,36,37,41,44,56,58,61,65,[71][72][73]97], the frequency of hematoma/ecchymosis after intracavernosal PGEi is calculated to be 1.5% (Table 5).…”
Section: Localmentioning
confidence: 99%
“…Padma-Nathan [11] did a blind study comparing PGE i + papaverine with phentolamine and PGEi with phentolamine, and concluded that the latter was superior. Floth and Schramek [12] compared the effect of papaverine + phentolamine with papaverine + PGEi; they also com pared PGE[ alone with papaverine + PGE[ and conclud ed that the combination of papaverine and PGEi was superior. In a review of the literature and their own expe rience, Buvat et al [2] list several factors that influence a patient's response to an intracavemous injection.…”
Section: Discussionmentioning
confidence: 99%